The mechanics of surgery; comprising detailed descriptions, illustrations and lists of the instruments, appliances and furniture necessary in modern surgical art - Truax, Charles, 1852- ([Hammond press, W. B. Conkey company], 1899)
Covers the use and origin of surgical instruments. The C. Truax firm was one of the premier instrument makers in 19th century America.